Subcellular distribution and chemical forms of manganese in Daucus carota in relation to its tolerance - Kuang, Xueshao; Wang, Wumin; Hu, Jiayao; Liu, Wensheng; Zeng, Wenbin (Frontiers in Plant Science, 2022)
Daucus carota is a biennial herb of the Umbelliferae, which is a candidate plant for phytoremediation of Mn pollution. To reveal the mechanism of this plant to adapt to Mn stress, plant growth, anatomical structure, Mn accumulation characteristic, Mn subcellular distribution and chemical forms of D. carota under six Mn2+ concentrations by pot culture experiments were studied. The results showed that with the rising Mn concentrations, the total dry weight, leaf area of D. carota increased firstly and then decreased, while the specific leaf area increased. The thickness of main vein, upper epidermis, lower epidermis, the thickness of the palisade tissue, and the thickness of the spongy tissue of the leaves increased firstly and then decreased. The Mn content in the aboveground and underground parts of D. carota increased, and the values of bioconcentration factor (BCF) and the translocation factor (TF) exhibited higher than one. The Mn existed in cell wall and soluble components accounted for the largest proportion, and the proportion of Mn in the cell wall increased with increasing concentrations of Mn. In addition, Mn mainly existed in ethanol extraction state, deionized water extraction state and sodium chloride extraction state. The results showed that D. carota could alleviate the damage caused by high manganese concentration by storing most of manganese in cell wall and vacuole, and existing in the form of low-activity state.